Glowing mushrooms - Salim, Sabiha; Saadun, Norzanalia; Mat, Sapari; Rajihan, Siti Noor Shuhada; Md Sharif, Badrul Azhar (Universiti Putra Malaysia Press, 2017)
Have you ever ventured into the forest at night and saw glowing mushrooms on top of some wood surfaces? The glow or greenish lights from bioluminescent mushrooms come from a light-emitting substance called luciferin.